The Effect of Serotonin-Norepinephrine Reuptake Inhibitor Milnacipran on Anxiety-like Behaviors in Diabetic Mice - Tuhfatul Ulya; Chrismawan Ardianto; Mahardian Rahmadi; Dewi Wara Shinta; Junaidi Khotib (Universitas Airlangga, 2021)
Background: Diabetes mellitus is a chronic disease that causes neuronal plasticity and increased hypothalamic pituitary adrenal (HPA) axis of stress disorders. The change in metabolism is reportedly associated with inadequate response to antianxiety and antidepressant agents. Objective: This study aimed to determine the effect of milnacipran antidepressants on anxiety-like behavior in mice with diabetes mellitus. Methods: Male ICR mice were divided into naive, stress, diabetes mellitus (DM), DM + stress groups to measure anxiety-like behavior. Diabetes mellitus was induced using alloxan, and electric footshock stress was used as a stressor for 14 consecutive days. Anxiety-like behavior was measured using the light-dark box (LDB) and elevated plus maze (EPM) test at days 0, 7 and 14. The antidepressant milnacipran (MIL) was given for 7 days, on days 8 to 14. On day 14, evaluation of anxiety-like behavior after administration of MIL was carried out in all groups using LDB and EPM tests. Results: The results showed that administration of milnacipran effectively ameliorated anxiety-like behavior in the non-DM, but not in the DM group, using the LDB test. A similar result was demonstrated in the EPM test showing the non-DM group's attenuation after milnacipran administration. Conclusion: The present results indicate that there is an inadequate attenuation of the anxiety-like behavior after treatment with milnacipran in diabetes conditions.